Wages, Minimum Wage, and Trade Unions : A Czech Perspective - Bittner, Jan; Pavelka, Tomáš, 1975-; Dvouletý, Ondřej; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis empirically examines the role of two key labour market institutions—minimum wage and collective bargaining—in shaping working and living conditions in the Czech Republic. It consists of three related articles with the following objectives: (1) to analyse the impact of minimum wage increases on the structure of household consumption, (2) to evaluate the implications of the criteria defined in the European Directive on Adequate Minimum Wages for the Czech minimum wage, and (3) to estimate the effect of collective agreements on wages and wage inequality. The main methods used include the estimation of income elasticity using the OLS with testing for moderation effects to explore household responses to minimum wage changes, beta-convergence to analyse the development of minimum wages in Europe, and weighted least squares along with propensity score matching to estimate the union wage effect. The primary data sources are the Household Budget Surveys from 2011 to 2019 and the Average Earnings Information System for 2022. The findings indicate that households use additional income from minimum wage increases to cover essential needs. However, their budget share decreases, shifting consumption from nondurable to semidurable and durable goods. The presence of children moderates spending on services, suggesting a willingness to invest in education despite budget constraints. The reliance on essential consumption reflects the low level of the minimum wage. As shown by living wage calculations, it lacks sufficient purchasing power to meet basic needs. Aligning it with EU standards could benefit from binding wage-setting criteria in the EU Directive on Adequate Minimum Wages. The directive also seeks to strengthen the role of collective bargaining in wage determination.
With one of the EU’s lowest union densities and agreement coverage, Czech unions have weak bargaining power, resulting in a smaller effect of collective agreements on wages compared to other countries. The wage premium is most pronounced for the highest and lowest earners. These findings offer insights for strengthening labor market institutions and addressing gaps in Czech empirical research. They highlight the potential to raise the minimum wage to support low-income households and foster human capital investment. The limited union wage premium may explain persistently low wages, while stronger collective bargaining could offer potential for wage growth.
Vedoucí práce: Tomáš Pavelka
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management a manažerská ekonomie [obor disert. práce]; disertace; dissertations